KETAHANAN PAPAN KOMPOSIT DARI LIMBAH KAYU SENGON DAN KARTON TERHADAP RAYAP KAYU KERING DAN RAYAP TANAH (PERENNIAL, 2008)
This study was aimed to analyze the resistance of composites board made from wafer and carton or paper overlaid on drywood termite and subterranean termite. Materials used in this study were wafer from sengon wood (Paraserianthes falcataria L. Nielsen), water based polymer isocyanate adhesive, veneer, and several kind of carton and paper such as duplex carton, recycle carton, corrugate board, and waste of cement sack. The target density was 0.65 g/cm3, while the resin solid content was 6%. The result of this study showed that no significantly different on infection rate of drywood termite among of composite board types and solid wood. The weight loose of composites board were 1.2–3.8%, while solid wood was 2.7%. Composites board more favorable to infection Macrotermes gilvus than solid wood. The weight loose of composites board were 19.3 – 28.8%, while solid wood was 12.6%.Key words: Composites board, drywood termite, subterranean termite